The Impact of Middle Eastern Geopolitics on Global Inflation and Energy Market Stability in 2026 - Fahrozi; Dedi Siswanto; Ma'mun Mukhid (CV. Era Digital Nusantara, 2026)
This study examines the impact of Middle East geopolitical dynamics on global inflation and energy market stability in 2026. The research addresses the growing concern that escalating geopolitical tensions disrupt global energy supply and contribute to rising inflationary pressures. The objective of this study is to analyze the direct effect of geopolitical risk on global inflation, assess its influence on energy market volatility, and identify the mediating role of energy price fluctuations. This research employs a quantitative approach using panel data from approximately 30 countries over the period 2010–2026. Secondary data were collected from reliable international sources, including the World Bank, International Monetary Fund (IMF), and the Geopolitical Risk Index (GPR). Data analysis was conducted using panel regression models and mediation analysis to examine both direct and indirect relationships among variables. The findings reveal that geopolitical tensions in the Middle East significantly increase global inflation, both directly and indirectly through heightened energy market volatility. Energy price fluctuations act as a partial mediator, indicating that disruptions in oil supply amplify inflationary pressures across countries, particularly in energy-importing economies. The study also finds that inflation responses vary across countries depending on their level of dependence on global energy markets. In conclusion, this study highlights the critical role of geopolitical stability in maintaining global economic balance. Policymakers are encouraged to strengthen energy diversification strategies and enhance international cooperation to mitigate the economic risks associated with geopolitical conflicts.